The new model of foreign aid drawn from the experiences of Japan and the United States - Gustav Ranis; Stephen Kosack; Ken Togo (Yale University, Economic Growth Center, 2011)
This chapter compares Japan and the US as they provide different types of capital to the developing world, focusing especially on foreign aid and, to some extent, also on remittances and the role of NGOs. The main focus is on the quality of aid and on past conceptual differences and on an emerging convergence between these two major donors, with Japan having the potential advantage of being able to bring its own historical experience in development to bear.
Keywords: O11; O15; O16; O23; 330; foreign aid; remittances; NGO; Japan; US